2015
DOI: 10.1093/abbs/gmv045
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of sperm protein profile induced by cigarette smoking

Abstract: Cigarette smoking is associated with lower semen quality, but how cigarette smoking changes the semen quality remains unclear. The aim of this study was to screen the differentially expressed proteins in the sperm of mice with daily exposure to cigarette smoke. The 2D gel electrophoresis (2DE) and mass spectrometry (MS) analyses results showed that the mouse sperm protein profile was altered by cigarette smoking. And 22 of the most abundant proteins that correspond to differentially expressed spots in 2DE gels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Lowered expression of ATP5A1 reduces the ATP supply and leads to energy deprivation and affects the sperm motility. ATP5A1 was reported to be overexpressed in the high‐motility spermatozoa (Huang et al ., ) and underexpressed in reduced sperm motility (Chen et al ., ). In the current study, the downregulation of ATP5A1 reported by the proteomic analysis was validated by WB.…”
Section: Discussionmentioning
confidence: 97%
“…Lowered expression of ATP5A1 reduces the ATP supply and leads to energy deprivation and affects the sperm motility. ATP5A1 was reported to be overexpressed in the high‐motility spermatozoa (Huang et al ., ) and underexpressed in reduced sperm motility (Chen et al ., ). In the current study, the downregulation of ATP5A1 reported by the proteomic analysis was validated by WB.…”
Section: Discussionmentioning
confidence: 97%
“…Other possible mechanisms might be related to the negative impact of smoking on the 8 nAChR subunits found in human spermatozoa, resulting in smoking-related sperm damage [35]. In addition, different proteins (Aldoa, ATP5a1, Gpx4, Cs) expressed in sperms were significantly altered in smokers [36]. Cigarette smoking was found to also affect Ca 2+ - ATPase activity of the spermatozoa as well [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that the sperm protein profile in infertile men is altered, and some researchers have assessed these profiles in several male infertility conditions including varicocele (Agarwal, Sharma, Samanta, Durairajanayagam, & Sabanegh, ; Agarwal, Sharma, Durairajanayagam, Ayaz, et al., ; Agarwal, Sharma, Durairajanayagam, et al., ; Hosseinifar et al., ), obesity (Kriegel et al., ; Liu et al., ), smoking (Chen et al., ), failed fertilisation after assisted reproduction techniques (ART; Frapsauce et al., ; Legare et al., ; Pixton et al., ), asthenozoospermia (Amaral et al., ; Hashemitabar, Sabbagh, Orazizadeh, Ghadiri, & Bahmanzadeh, ; Liu et al., ; Martinez‐Heredia, de Mateo, Vidal‐Taboada, Ballesca, & Oliva, ; Parte et al., ; Shen, Wang, Liang, & He, ; Siva et al., ; Zhao et al., ) and idiopathic infertility (Legare et al., ; McReynolds et al., ; Xu et al., ). Sperm protein profiles have also been evaluated in men with semen oxidative stress (Ayaz et al., ; Sharma et al., ) and sperm DNA fragmentation (Intasqui et al., ; de Mateo et al., ), which are common causes of male infertility.…”
Section: Introductionmentioning
confidence: 99%